Estimation of brain receptor occupancy for trazodone immediate release and once a day formulations. Issue 6 (2nd March 2022) - Oggianu, Laura; Di Dato, Giorgio; Mangano, Giorgina; Rosignoli, Maria Teresa; McFeely, Savannah; Ke, Alice Ban; Jones, Hannah M.; Comandini, Alessandro
Abstract: Trazodone is approved for the treatment of major depressive disorders, marketed as immediate release (IR), prolonged release, and once a day (OAD) formulation. The different formulations allow different administration schedules and may be useful to facilitate patients' compliance to the antidepressant treatment. A previously verified physiologically‐based pharmacokinetic model based on in vitro and in vivo information on trazodone pharmacokinetics was applied, aiming at predicting brain receptor occupancy (RO) after single and repeated dosing of the IR formulation and repeated dosing of the OAD formulation in healthy subjects. Receptors included in the simulations were selected using static calculations of RO based on the maximum unbound brain concentration (Cmax, brain, u ) of trazodone for each formulation and dosing scheme, resulting in 16 receptors being simulated. Seven receptors were simulated for the IR low dose formulation (30 mg), with similar t onset and duration of coverage (range: 0.09–0.25 h and 2.1–>24 h, respectively) as well as RO (range: 0.64–0.92) predicted between day 1 and day 7 of dosing. The 16 receptors evaluated for the OAD formulation (300 mg) showed high RO (range: 0.97–0.84 for the receptors also covered by the IR formulation and 0.73–0.48 for the remaining) correlating with affinity and similar duration of time above the target threshold to the IR formulation (range: 2–>24 h). The dose‐dependent receptor coverage supports the multimodal activity of trazodone, which may further contribute to its fast antidepressant action and effectiveness in controlling different symptoms in depressed patients.